2017
DOI: 10.1080/10454446.2017.1266555
|View full text |Cite
|
Sign up to set email alerts
|

Young Chinese and Functional Foods for Mobility Health: Perceptions of Importance, Trust, and Willingness to Purchase and Pay a Premium

Abstract: Consumers' desire to enhance diet and health has become a driver for the development of functional food products. China, with one of the largest markets in the world, offers huge potential for these foods. In the context of functional foods, specifically related to mobility health, this study aimed to understand Chinese consumers' perceptions of the importance of these foods, trust, and willingness to purchase and pay a premium for such foods. A mixed-methodological approach using both focus groups and a surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 32 publications
3
40
0
Order By: Relevance
“…Extensive research has examined various factors that influence consumer trust, including trust in supply chain actors, assurance and regulatory systems, and the economic development status of the producing country [14,16,17,[27][28][29][30]. While these efforts have advanced our understanding of consumer trust, much of the previous studies have focused on particular aspects of trust in food and the food system, with some findings being country and culture specific [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has examined various factors that influence consumer trust, including trust in supply chain actors, assurance and regulatory systems, and the economic development status of the producing country [14,16,17,[27][28][29][30]. While these efforts have advanced our understanding of consumer trust, much of the previous studies have focused on particular aspects of trust in food and the food system, with some findings being country and culture specific [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that, in certain cases, consumers were only willing to pay a limited premium price. For example, Mirosa and Mangan-Walker [61] found Chinese consumers were not willing to pay more than 40% extra for functional foods, and Menrad [64] found that European consumers would only pay 30-50% extra for functional foods.…”
Section: Pricementioning
confidence: 99%
“…Some studies examined how consumers perceived either base product or added ingredients (B€ ackstr€ om et al, 2003;Frewer et al, 2003;Cox et al, 2004;Messina et al, 2008) in silos, while other studies assessed the combined effect of base and added ingredient on functional food perception (Bech-Larsen and Grunert, 2003;Mirosa and Mangan-Walker, 2018). Several other studies examined the issue of whether the communication of health benefits of functional foods would change consumers' attitude towards functional foods (Bech-Larsen and Grunert, 2003;Tudoran et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies examined the issue of whether the communication of health benefits of functional foods would change consumers' attitude towards functional foods (Bech-Larsen and Grunert, 2003;Tudoran et al, 2009). Scholars have explored whether increasing the intensity , authenticity Masson et al, 2016;Mirosa and Mangan-Walker, 2018), medium (Tudoran et al, 2009;Saba et al, 2010) and the type of health claims van Kleef et al, 2005) would affect functional food perception. Figure 1, that follows, is a representation of the literature on functional food dimensions.…”
Section: Introductionmentioning
confidence: 99%